The role of nurses in child abuse situations: a systematic review - Bomi Kim; Sunyeob Choi (Child Health Nursing Research, 2025)
Purpose Nurses play a crucial role in cases of victims of child abuse; however, but there is a need for a comprehensive understanding of their specific roles, responsibilities, and best practices is needed. Methods This integrative review aims to synthesize existing evidence on the role of nurses in cases of victims of child abuse. A literature search was conducted using PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), PsycINFO, and Scopus databases. A literature search was conducted using PubMed, CINAHL, PsycINFO, and Scopus databases. This review included 12 qualitative and quantitative studies. Results This review identified the following four themes: nurses’ responsibility, intention to report child abuse, perceptions of child abuse, and risk assessment of child abuse. The findings revealed that nurses play a multifaceted role in child abuse situations. Evidence-based practices and guidelines were identified to optimize recovery outcomes among children who have experienced abuse. Conclusion This integrative review contributes to the body of knowledge on nurses’ role in cases of victims of child abuse by providing valuable insights for nursing practice, education, and policy. These findings can help guide nurses in developing evidence-based interventions and collaborative approaches to support the recovery of victims of child abuse.